Performance Evaluation of Conventional and Neural Network-Based Decoder for an Audio of Low-Girth LDPC Code - Dharmeshkumar Patel; Ninad Bhatt (Journal of Electrical and Computer Engineering)
Noise in a communication system degrades the signal level at the receiver, and as a result, the signal is not properly recovered or eliminated at the receiver side. To avoid this, it is necessary to modify the signal before transmission, which is achieved using channel coding. Channel coding provides an opportunity to recover the noisy signal at the receiver side. The low-density parity-check (LDPC) code is an example of a forward error correcting code. It offers near Shannon capacity approaching performance; however, there is a constraint regarding high-girth code design. When the low-girth LDPC code is decoded using conventional methods, an error floor can occur during iterative decoding. To address this issue, a neural network (NN)-based decoder is utilized to overcome the decoding problem associated with low-girth codes. In this work, a neural network-based decoder is developed to decode audio samples of both low- and high-girth LDPC codes. The neural network-based decoder demonstrates superior performance for low-girth codes in terms of bit error rate (BER), peak signal-to-noise-ratio (PSNR), and mean squared error (MSE) with just a single iteration. Audio samples sourced from the NOIZEUS corpus are employed to evaluate the designed neural network. Notably, when compared to a similar decoder, the decoder developed in this study exhibits an improved bit error rate for the same signal-to-noise ratio.